Performance comparison of Ni-Fe loaded on NH2-functionalized mesoporous silica and beach sand in the hydrotreatment of waste palm cooking oil. Issue 6 (December 2020) - Trisunaryanti, Wega; Larasati, Savitri; Bahri, Syaiful; Ni'mah, Yatim lailun; Efiyanti, Lisna; Amri, Khairil; Nuryanto, Rahmad; Sumbogo, Satriyo D.
Graphical abstract: Highlights: Parangtritis Beach sand can be directly used as hydrotreating catalyst. Adding Ni and APTMS to sand structure (Ni-NH2 -Sand) improves its catalytic activity. Ni-NH2 -Sand can produce similar activity as mesoporous silica (MS) catalyst. Ni-NH2 -MS exhibits better activity than Ni-Fe-NH2 -MS. Ni-NH2 -Sand catalyst produces high selectivity towards diesel-range hydrocarbon. Abstract: Preparing the commonly-used mesoporous silica (MS) catalyst support from a natural source involves a step-by-step extraction process which requires the use of chemical reagents that are harmful for the environment. Based on this consideration, a direct use of natural ingredient for catalysis support without prior extraction is very interesting to look into. In the present work, the catalytic performance of Ni supported on amine-functionalized beach sand (Ni-NH2-Sand) was thoroughly compared with the activity of three MS-supported catalysts ( i.e. Ni-NH2 -MS, Fe-NH2 -MS, Ni-Fe-NH2 -MS) in the hydrotreatment of waste palm cooking oil at 450 ℃. All catalysis materials were synthesized from Parangtritis Beach Sand comprising Fe2 O3 (31.75 wt%), SiO2 (43.09 wt%), and Al2 O3 (12.91 wt%). This study found that among all MS-supported catalysts, monometallic Ni-NH2 -MS comprising 2.29 wt% of Ni generated the highest liquid hydrocarbon yield with over 64.44 wt% conversion. Achieving such a comparable result was possible for sand-supported catalyst by adding 10 times more Ni loading than Ni-NH2 -MS. This was shown by the 66.83 wt% liquid hydrocarbon that was successfully collected from the hydrotreatment of waste palm cooking oil in the presence of Ni-NH2 -Sand catalyst containing 20.75 wt% Ni, 27.28 % Fe2O3, and 16.76 wt% SiO2 . The result describes a potential use of sand as an alternative catalyst to produce green fuel.